Communication technologies for Smart Water Grid applications: overview, opportunities, and research directions - Lalle, Yandja (2021)
Due to the aging of current water infrastructure and the increased demand for water resources, water distribution systems encounter several problems such as pipes leaks and bursts, water contamination or pollution, and water optimization issues. To cope with these issues, access to water-related data and information related to the water grid is fundamental in order to build sophisticated strategies for water management. Integrating Information and Communication Technologies (ICT) into the current water infrastructure is one viable solution to access to water-related data. This new infrastructure that integrates ICT into the water distribution system is called Smart Water Grid (SWG). The information layer of the SWG requires well-suited communication networks. This paper reviews wireless communication technologies that can be exploited for the implementation of SWG applications. The paper mainly focuses on the exploration of Low Power Wide Area Networks (LPWANs) that promise to overcome problems confronted by communication technologies used currently in SWG applications. Some of the wireless technologies used in SWG applications suffer from high power consumption issues while others are limited in terms of communication range. For future SWG applications, in this work we recommend LPWAN technologies due to their low power consumption, long communication range and excellent radio penetration. A range of challenges and research directions regarding the recommended LPWANs is also discussed.